2016
DOI: 10.1002/adfm.201604465
|View full text |Cite
|
Sign up to set email alerts
|

Materials and Device Designs for an Epidermal UV Colorimetric Dosimeter with Near Field Communication Capabilities

Abstract: Ultraviolet (UV) solar radiation is a leading cause of skin disease. Quantitative, continuous knowledge of exposure levels can enhance awareness and lead to improved health outcomes. Devices that offer this type of measurement capability in formats that can seamlessly integrate with the skin are therefore of interest. This paper introduces materials, device designs, and data acquisition methods for a skin‐like, or “epidermal,” system that combines colorimetric and electronic function for precise dosimetry in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 23 publications
0
124
0
Order By: Relevance
“…Applications range from those in hospital care and clinical medicine to physical rehabilitation, fitness/wellness tracking, awareness and cognitive state assessment, and human-machine interfaces (7, 8). Although use of an individual device on a targeted region of the body enables clinically validated measurement modalities in electrophysiology, temperature, pressure, blood oximetry, and others, using multiple separate devices across different anatomical locations simultaneously could expand the possibilities to enable measurements across the body for tracking of position-dependent body processes, disease states, and/or external stimuli (8, 9). …”
Section: Introductionmentioning
confidence: 99%
“…Applications range from those in hospital care and clinical medicine to physical rehabilitation, fitness/wellness tracking, awareness and cognitive state assessment, and human-machine interfaces (7, 8). Although use of an individual device on a targeted region of the body enables clinically validated measurement modalities in electrophysiology, temperature, pressure, blood oximetry, and others, using multiple separate devices across different anatomical locations simultaneously could expand the possibilities to enable measurements across the body for tracking of position-dependent body processes, disease states, and/or external stimuli (8, 9). …”
Section: Introductionmentioning
confidence: 99%
“…These flexible filters obtained in this study not only illustrate their utilities to modulate device performance when integrating with microscale LEDs and PV detectors, but also exhibit ideal biocompatibilities both in vitro and in vivo. As an essential optical component, such filters can be readily implemented into wearable and implantable optoelectronic systems for biomedical uses, including fluorescence sensing, optogenetic interrogation, and health monitoring . Besides LEDs and photodetectors, such filters can also be combined with other photonic devices such as microscale lasers and waveguides for versatile applications like beam steering and spectral shaping .…”
Section: Resultsmentioning
confidence: 99%
“…Advanced optoelectronic devices play an important role in biomedical fields like bioimaging, epidermal sensing, phototherapy, and laser surgery . More recently, researchers have been investing considerable efforts in the exploitation of implantable optoelectronic devices and systems, which have capabilities to deliver and receive optical power and signals directly within the deep tissue.…”
Section: Introductionmentioning
confidence: 99%
“…A number of organisms use high energy UV radiations for adaptive camouflage with concealment, [ 1–3 ] protection, [ 4–6 ] or signaling, [ 7–9 ] through the mechanisms of photonic crystal, [ 10 ] surface morphological control, [ 5,11 ] chemical fluorophore, [ 7,9,12 ] and radiation reflection. [ 8,13,14 ] There have been many attempts to mimic such radiation‐responsive color changes and several studies demonstrated responsive display, [ 15–17 ] encryption, [ 18,19 ] colorimetric sensors, [ 20,21 ] and data recording. [ 22,23 ] Unfortunately, such color changing systems are useful only in the presence of bright external light.…”
Section: Figurementioning
confidence: 99%